Gambaran Pola Makan Anak Baduta Pendek di Desa Pasongsongan (Wilayah Pesisir Kabupaten Sumenep) - Soesanti, Inne (Gorontalo Journal of Public Health, 2019)
Toddler stunted problems describe the existence of chronic nutritional problems, ranging from the womb to the age of 2 years. This study aims to describe the eating patterns stuntted the toddlers in Pasongsongan Village. This study was used qualitative approach. The informants was determined by purposively, with informants were grandmothers or mothers who have grandchildren or stunting children, traditional healer/herbalist, posyandu cadre, public community. Data collection using interview and observation techniques. The result was showed stunted toddlers who were given food in the porridge form until the age of one year, rice cake and soup without side dishes and vegetables. These foods were given on the grounds that the intestine of the child was not strong in receiving rough food. Animal foods were given a compilation of 12 months selected children classified as late. Sea fish was given after the child can walk, with the reasons toddlers can get infection intestinal worms. Wormy myth was very trusted by the informants, that cause most of them not give sea fish to their children before the age of one years. Practices to give food with high  carbohydrate water and low protein dense. The conclusion was the lack of protein sources such as egg, sea fish, and chicken in both quality and quantity can be a factor that cause stunting in the children under two years old. The suggestions for the children under two years old must be given food sources of protein, and given information for the mother about knowledge the benefits of consuming fish for children under the age of two years.Masalah balita pendek menggambarkan adanya masalah gizi kronis, mulai dari dalam kandungan sampai usia 2 tahun. Penelitian ini bertujuan untuk mengeksplorasi pola makan anak baduta pendek di Desa Pasongsongan. Penelitian ini menggunakan pendekatan kualitatif. Penentuan informan secara purposive, dengan informan adalah nenek atau ibu yang mempunyai cucu atau anak baduta yang stunting, dukun/pembuat jamu, kader posyandu dan tokoh masyarakat. Pengumpulan data dengan teknik wawancara dan observasi. Hasil penelitian menunjukkan anak baduta stunting diberikan makanan berupa bubur sampai usia satu tahun, lontong dan kuah tanpa lauk dan sayur, makanan-makanan tersebut diberikan dengan alasan usus anak belum kuat menerima makanan yang kasar. Makanan hewani diberikan ketika anak berusia 12 bulan tergolong terlambat. Ikan laut diberikan setelah anak bisa berjalan, dengan alasan takut anak terkena cacingan. Mitos cacingan sangat dipercaya oleh para informan, sehingga banyak yang tidak memberikan ikan laut kepada anaknya sebelum usia satu tahun. Pemberian makanan lebih banyak mengandung karbohidrat dan air serta rendah protein. Kesimpulan dari penelitian ini adalah kurangnya pemberian sumber protein seperti telur, ikan laut, dan daging ayam baik secara kualitas maupun kuantitas dapat menjadi faktor yang menyebabkan stunting pada anak baduta. Saran yang diberikan bahwa anak di bawah usia dua tahun harus diberikan makanan sumber protein, dan kepada ibu balita perlu diberikan informasi terkait pengetahuan mengenai manfaat mengkonsumsi ikan bagi anak di bawah usia dua tahun.